# Algebra

log3 (2x – 1) – log3 (x – 4) = 2

1. 👍 0
2. 👎 0
3. 👁 486
1. log3 (2x – 1) – log3 (x – 4) = 2 , clearly x > 4

(2x-1)/(x-4) = 3^2
2x^2 -9x-5 = 0
(2x+1)(x-5) = 0
x = -1/2 or x = 5

but x > 4, so

x = 5

1. 👍 0
2. 👎 0

## Similar Questions

1. ### maths

express log9 in terms of log3 x and log3 y and solve for x and y simultaneously

2. ### Math

Given that x=log3^5 and y=log3^2, rewrite log3^60 in terms of x and y.

Log3(x)=log9(6x)

4. ### mathematics

log3(4x+1)-log3(3x-5)=2

1. ### trig

solve for x log4 64+ log2 2 ________________ =x log3 81

2. ### algebra 2 trig

if log3=a then log300 can be expressed as? 1) 100a 2)a+2 3)100+a 4)3a

3. ### Pre Calculus

Evaluate the function f(x) = log3 x at x =1/27 without using a calculator a. –4 b. –2 c. 1/27 d. –3 e. 27

4. ### calculus

1) Solve for x in terms of k: log3(x) + log3(x+7) = k; 3 is the base 2) e^(x+5) = e^(x) + 6, solve for x. Please help, I have no idea how to do these and I've tried several times!

1. ### algebra

(2*log7 16)/(log3(√10+1)+log3(√10-1)log7 2

2. ### Algebra 1

Explain the differences between solving these two equations: •log3(x - 1) = 4 AND log3(x - 1) = log34 I think it has to deal with the formulas?

3. ### Math

logx(9x^2)[log3(x)]^2=4 i got the x=1/9 and x=3 is that correct?

4. ### Trigonometry

log3(x^2)=2log3(4)-4log3(5)